APEX SCHOLAR TO BE A USM BRAND - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 27 May 2016 – The APEX Scholar Programme, initiated under the fiveyear development framework of Universiti Sains Malaysia (USM) would be a new brand to reflect the excellence of the university.